Look Here! Measuring the Attentional Demand of Near-Future Full Windshield Vehicle Displays - Topliss, Bethan (2023)
Driving a road vehicle is a task which requires and demands visual attention. Despite this, information on a vehicle’s state, the road environment, or the entertainment features have commonly been conveyed to the driver via visual means because the information can quickly be received and responded to as desired by the driver. Current vehicle displays commonly consist of digital displays presented in the centre console (between the two front seats, under the windshield), and at the instrument cluster (above the steering wheel). Such displays are sometimes referred to as Head-down Displays (HDDs) as they encourage the driver to look down and within the vehicle. The attentional demand and corresponding distraction arising from HDDs is a longstanding component of research largely due to safety concerns. Conducting secondary tasks with such displays (where the driver performs a task in addition to primary task of driving e.g., changing the vehicle’s climate controls) is associated with degraded driving performance and therefore an increased crash risk. More recent developments in display technology have led to the inclusion of Head-up Displays (HUDs) within vehicles. These displays present imagery in a translucent form over the road environment typically by reflecting or projecting graphics onto the windshield or another treated glass component. Since they position information closer to the drivers’ view of the road environment, they are considered to encourage more beneficial attentive behaviours than HDDs, by ensuring the driver is looking up and out of the vehicle towards the road ahead. HUDs within road vehicles are expected to expand in size so that information can be presented across the whole windshield; these are commonly referred to as a full Windshield Displays (WSDs). Presently, the types of tasks that have been investigated on these displays have been limited. Equally, the attentional demand of these novel displays needs to be ascertained, as well as how this varies when imagery has the potential to be located across the whole windshield. Consequently, this thesis aimed to: establish the demand of near-future ecologically valid tasks on windshield displays, develop approaches to investigate visual demand, and ascertain how this demand varies when imagery is presented across expansive windshield locations. A series of four driving simulator-based studies were conducted to address these aims. The first study examined twenty-six participants using an after-market HUD device at the Virginia Tech Cogent Lab. Participants completed tasks on the display which contained components likely to be within the interfaces of near-future HUDs or WSDs (text reading and menu navigation). The analysis showed interactions between task type and the task complexity significantly impacted driver eye-movement and specific longitudinal measures of driving performance. Thus, the exact attributes of the tasks presented on a HUD appear to influence the display’s attentional demand. The second study used two after-market HUD devices to simulate display imagery appearing across the windshield. Twenty-six participants were recruited, and a visually demanding task was used to begin to assess visual demand across windshield displays. The measures showed that increasing display eccentricity resulted in poorer driving performance, thereby indicating greater demand. The third study recruited sixty participants to expansively investigate the impact of display imagery presented in fifty-one display locations. The WSD was simulated using projection. An innovative approach was developed to establish how long a driver could make a continuous glance to these locations before unsafe driving occurred. Graphical depictions of these time thresholds were produced for several dependent measures; they illustrate the visual demand implications of displays across the windshield area. The final study recruited eighteen participants to compare three display locations (two windshield displays and a HDD). Two display tasks were used to establish how drivers manage their engagement with these displays. The observed interactions indicated that drivers were more enticed to attend to the windshield displays than the HDD. Overall, this thesis demonstrates novel approaches to assessing visual demand across display positions. It concludes that windshield display demand is dependent on display location eccentricity and the nature of the task being displayed. The outcome of this demand depends on how drivers respond to these features. Finally, future work and the future of vehicle displays is discussed.